Hubungan Content Marketing Bittersweet By Najla dengan Keputusan Pembelian Followers - Rizkia Azzahra Hendrawan; Yulianti (Jurnal Riset Manajemen Komunikasi, 2022)
Abstract. @bittersweet_by_najla, uses Instagram as a promotional medium. This study was conducted to determine the relationship between content marketing bittersweet by najla and followers' purchasing decisions. The theory used in this research is New Media Social Media Marketing. This study uses quantitative research methods. Data collection techniques used in the study were through observation, literature study, and distributing questionnaires or questionnaires. The population used are followers of bittersweet by najla , 100 people. The results in this study are that there is a relationship between content marketing bittersweet by najla and the purchase decision of followers. Abstrak. @bittersweet_by_najla, menggunakan Instagram sebagai media promosi. Penelitian ini dilakukan untuk mengetahui hubungan content marketing bittersweet by najla dengan keputusan pebelian followers. Teori yang digunakan dalam penelitian ini adalah New Media Social Media Marketing. Penelitian ini menggunakan metode penelitian kuantitatif. Teknik pengumpulan data yang digunakan adalah observasi, studi pustaka, dan kuesioner. Populasinya followers bittersweet by najla, 100 orang. Hasil dalam penelitian ini adalah terdapat hubungan content marketing bittersweet by najla dengan keputusan pembelian folowers